2010
DOI: 10.5204/intjfyhe.v1i1.21
|View full text |Cite
|
Sign up to set email alerts
|

Transforming the first year learning experience through research based media practice

Abstract: <p>This paper reports on a case study in which the course coordinator attempted to introduce research into the first year media arts curriculum in an effort to engage students through an enquiry learning approach. The findings from student evaluations conducted over a five year period reveal the challenges as well as the benefits to learners. The increase in student mean scores for evaluation criteria together with student qualitative comments in response to evaluations conducted following redesign of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The English study concluded that the early use of open-ended or problem-based learning, which superficially might appear helpful to teach about research, "given the potential vulnerability of first-year students … should be carefully structured and supported" (Turner et al 2017, p.818). Interestingly, an Australian case study similarly tracking the sometimes challenging introduction of inquiry-led learning into a media studies program, over five years and iterations, concluded with similar advice (Wood, 2010).…”
Section: Literature and Contextmentioning
confidence: 85%
See 2 more Smart Citations
“…The English study concluded that the early use of open-ended or problem-based learning, which superficially might appear helpful to teach about research, "given the potential vulnerability of first-year students … should be carefully structured and supported" (Turner et al 2017, p.818). Interestingly, an Australian case study similarly tracking the sometimes challenging introduction of inquiry-led learning into a media studies program, over five years and iterations, concluded with similar advice (Wood, 2010).…”
Section: Literature and Contextmentioning
confidence: 85%
“…In a wider international exploration of academics' perceptions of the necessary skills for, and hindrances to, early-undergraduate research learning in geography (Walkington et al, 2011) similar barriers persisted and others appeared. They included large classes, students' lack of confidence, passivity and limited research skills (also Guo, Loy & Banow, 2018;Wood, 2010). Recent literature examining firstyear undergraduates' induction and learning experiences echo such challenges.…”
Section: Literature and Contextmentioning
confidence: 99%
See 1 more Smart Citation